Policy and regional science: Key drivers of agricultural development in Africa - International Livestock Research Institute (International Livestock Research Institute, 2011)
Bio-Innovate can improve regional science and technology development by being based at the BecA facilities, where they can showcase what new technology can do for agricultural development in east Africa. The project can also make a tremendous difference by being connected with the product and technology champions at universities and other public institutions in the region, and through strong links with local science and technology councils, which are the main drivers of new policies (John Komen, Assistant Director of the Program for Biosafety Systems, at the International Food Policy Research Institute (IFPRI)). Description: Video recorded at the Launching of Bio-Innovate Programme, ILRI, Nairobi, 16 March 2011.